2021
DOI: 10.1111/csp2.535
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the COVID‐19 pandemic on amphibian road mortality

Abstract: The COVID-19 pandemic and its related human activity shutdowns provide unique opportunities for biodiversity monitoring through what has been termed the "anthropause" or the "great human confinement experiment." The pandemic caused immense disruption to human activity in the northeastern United States in the spring of 2020, with notable reductions in traffic levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 47 publications
(67 reference statements)
1
18
0
Order By: Relevance
“…This included closure or restriction of beach use for recreational purposes resulting in beaches almost devoid of beachgoers for at least 3 months and very low frequency for several months. At first, authors reported that reduced human activity during COVID-19 termed “anthropause” was positive, resulting in fewer human-wildlife encounters, higher breeding success of resident species, and improved ecosystem condition worldwide ( Manenti et al, 2020 ; LeClair et al, 2021 ; Soto et al, 2021 ). However, negative impacts stemming from COVID-19 shutdowns have also been reported, including the increasing in beach pollution by personal protective equipment ( Ben-Haddad et al, 2021 ; Thiel et al, 2021 ) and spreading of illegal activities such as vehicle traffic due to reduction in law enforcement ( Manenti et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This included closure or restriction of beach use for recreational purposes resulting in beaches almost devoid of beachgoers for at least 3 months and very low frequency for several months. At first, authors reported that reduced human activity during COVID-19 termed “anthropause” was positive, resulting in fewer human-wildlife encounters, higher breeding success of resident species, and improved ecosystem condition worldwide ( Manenti et al, 2020 ; LeClair et al, 2021 ; Soto et al, 2021 ). However, negative impacts stemming from COVID-19 shutdowns have also been reported, including the increasing in beach pollution by personal protective equipment ( Ben-Haddad et al, 2021 ; Thiel et al, 2021 ) and spreading of illegal activities such as vehicle traffic due to reduction in law enforcement ( Manenti et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The anthropause-provided opportunities to study the effects of traffic on wildlife are already paying dividends, with noted reductions in WVCs (Manenti et al, 2020;Abraham and Mumma, 2021;Bates et al, 2021;Bil et al, 2021;Driessen, 2021;LeClair et al, 2021;Shilling et al, 2021;Łopucki et al, 2021) and rapid behavioral shifts that may increase fitness (Derryberry et al, 2020). We further posit additional potential changes to species interactions, behavior, fitness, animal distributions and gene flow due to the global respite from traffic impacts (Figure 2).…”
Section: The Global Wildlife-vehicle Collisions Observatorymentioning
confidence: 89%
“…The most dramatic reductions in traffic (Figure 1), coincided with a period of high mobility for many species in the northern hemisphere: the breeding season and migration period. Amphibians, the most seriously declining taxa on Earth, normally suffer huge road mortality due to site philopatry (Beebee, 2013), but the largest reduction in traffic coincided with their peak period of movement, which appears to have translated into significantly reduced amphibian mortality in some countries (Manenti et al, 2020;Bates et al, 2021;LeClair et al, 2021).…”
Section: An Anthropause-mediated Reduction In Wildlife-vehicle Collis...mentioning
confidence: 99%
See 2 more Smart Citations